The role of FLNC in the contractility of the heart and valve development in zebrafish - Alshahrani, Areej Ali, author; Garrity, Deborah, advisor; Mueller, Rachel, committee member; Bark, David, committee member (Colorado State University. Libraries, 2020)
Dilated Cardiomyopathy (DCM) is the most common type of cardiomyopathy disease that causes heart muscle defects. DCM is characterized by a dilated left ventricular chamber and systolic dysfunction that results in congestive heart failure. Although the cause of DCM is not fully understood, evidence supports the hypothesis that costameric proteins contribute to muscle dysfunction linked to cardiomyopathy. In fact, the mutation of FLNC has been linked to many muscle disease including myofibrila myopathies (MFM) and different types of cardiomyopathy. However, the mechanisms underlying the variability between MFM and cardiac disease is a field of interest. Patients with DCM shown to carry truncating variants whereas patients with hypertrophic cardiomyopathy (HCM) carried missense variants. Additionally, patients with other types of cardiomyopathy carried missense or in-frame indel variants (Ader, Groote et al.). This seems to suggest that different mechanisms may be at play regarding the role of FLNC in cardiac developments and they remain unclear. It would be interesting to examine if a similar correlation holds in animal model like zebrafish. Therefore, our group has developed the zebrafish model for study of the FLNC contribution to cardiac phenotypes. Here, we used several FLNC mutant lines to investigate how FLNC directly or indirectly affects development of the atrioventricular (AV) valve. To date, little data indicate whether or not increased RFF is pathologic. This project will test the overarching hypothesis that flnc depletion causes changes in RFF, which lead to aberrant valve development, which in turn affects overall heart function. We find that the cardiac morphological phenotype of most single FLNC alleles showed normal heart parameters such as heart rate, stroke volume, cardiac output and reverse flow fraction. However, flcnbexon14-/- allele exhibited a decreased in stroke volume and cardiac output whereas RFF is intact. Furthermore, using an immunocytochemistry to examine a correlation that may exist between the strength of the cardiac phenotype and the presence of valve defects indicate that valve defects presented in flncb truncation mutants, and suggest that defects in flncbexon35-/- embryos are more severe. In support of this finding, our qPCR study displayed that expression levels of klf2a and klf2b in flncaexon1-/- ; flncbexon14-/- double mutant hearts were significantly decreased. In addition, Prior studies have proposed that massive formation of intracellular protein aggregates imposes toxic impacts that contribute to the skeletal muscle degeneration observed in myofibrillar myopathy (Fichna, Maruszak et al. 2018). We demonstrated that the truncated protein either exerts a direct toxic effect, and/or sequesters wildtype FLNC leading to insufficiency phenotypes.
Keywords: filamin C; valve development; dilated cardiomyopathy; zebrafish; heart